(untitled) (Indian Journal of Public Health Research & Development, 2024)
BACKGROUND: Hypertension is one of the most commonly encountered chronic diseases, therefore treatment for the same should be affordable. Antihypertensive drugs of the same strength are available in the market at different costs. This study was conducted to raise awareness among health care workers and patients about the cost difference between different brands of the same antihypertensive drug, so that whenever possible a cheaper effective brand can be prescribed to ensure better patient adherence. METHODS: Maximum retail price(MRP) of various antihypertensive drugs of same strength , manufactured by different pharmaceutical companies was obtained from various offline and online sources.The minimum and maximum costs of 10 tablets/capsules noted.The cost ratio & percentage cost variation was calculated for single drugs and fixed dose combinations.The ceiling price(as per DPCO)of common antihypertensives (as per national list of essential medicines)was compared with their maximum cost. RESULTS: The formulations of single antihypertensive drugs and fixed drug combinations of two drugs were included in the study. Among the single antihypertensives analyzed the highest cost variation was of metoprolol (50mg) as high as 12144.89%.The cost ratio was seen to be seen to be highest for Metoprolol 50mg ER(80.3) followed by Metoprolol 25mg (78.4), Telmisartan 40mg(67).Among fixed dose combinations of two drugs analyzed highest cost variation was found that of Amlodipine 5mg + Atenolol 50mg combination(9566.6%) CONCLUSIONS: There was a huge price variation among the antihypertensive drugs manufactured by various companies for the same strength.Some measures thus,must be taken by the government to bring the uniformity in the price that will help to reduce the economic burden on the patients.